ANALISIS DAMPAK ZAKAT PRODUKTIF TERHADAP KEMISKINAN DENGAN MODEL CIBEST (STUDI KASUS YAYASAN BAITUL MAAL PERUSAHAAN LISTRIK NEGARA UNIT PELAKSANAAN PELAYANAN PELANGGAN PONOROGO PENYALURAN TAHUN 2020) - kusumaningati, nungky (Diponegoro Journal of Islamic Economics and Business, 2023)
This study aims to analyze the effect of productive zakat on reducing material poverty and spiritual poverty of mustahik. The results of the study based on the analysis of poverty indicators showed that the utilization of productive zakat was able to reduce the value of the mustahik poverty indicator. The results of the CIBEST model analysis show that the utilization of productive zakat can reduce the material and spiritual poverty of mustahik. The results of the paired t-test analysis showed a positive difference in material poverty and spiritual poverty of mustahik, before and after receiving productive zakat assistance from YBM UP3 PLN Ponorogo.